Lestvice, ki se uporabljajo pri ocenjevanju izida po zlomu kolka - Rauter Pungartnik, Tanja (Rehabilitacija (Ljubljana), 2008)
Aim: To report about different scales used to evaluate patient with hip fracture. Methods: To review literature. Conclusions: To evaluate the patient with hip fracture we can use different scales. Some of them evaluate only one area (body structures, body functions, participation and environmental factors, quality of life), some of them evaluate more levels and we can get more integrated image of injured person. Majority of scales is general and used also at other pathological conditions. These scales are complementary tool and they can not replace physical examination, but they are more accurate than just clinical impression.The combination of clinical experience and these scales may contribute to a better care of patients with hip fracture.
Keywords: kolčni sklep; zlomi; lestvice; ocenjevanje izida; starostniki